Chemodynamics of blue compact dwarf galaxies - Campuzano Castro, Federico (2016)
This work presents a brief summary of the analysis we are performing on the physical and chemical properties of the ionizing gas in star-forming regions belonging to two Blue Compact Dwarf galaxies (BCDs), using high resolution echelle spectra. Our aim is to perform a detailed study of the Chemodynamics on BCDs. To do that, we use our own Python code using the LMFIT (Non-Linear Least-Squares Minimization and Curve-Fitting for Python) package. We deconvolve the emission-line profiles fitting several gaussians to the different kinematical components to be able to estimate the properties and the nature of the ionized gas. Our next step is to use the kinematical information to perform the chemical abundance analysis and to infer the physical properties of the gas (the chemodynamical study) by using the methodology published in Hägele et al. (2008, 2012).